Perlindungan Hukum bagi Masyarakat Adat atas Penjualan Tanah Ulayat tanpa Persetujuan Kaum di Kabupaten Solok - Arbi, Imam; Yuhelson, Yuhelson; Hutomo, Putra (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2025)
Discussion on legal protection for indigenous peoples regarding the sale of customary land without the consent of the community in Solok Regency. The research was conducted using normative methods supported by interviews with normative juridical research types. The results of the study concluded that the implementation of customary land registration whose ownership is communal/joint in the Minangkabau community has no regulations governing it. This has resulted in obstacles and controversies in customary land ownership in Minangkabau, West Sumatra. It is recommended that the government, especially Solok Regency, issue regulations that can protect customary law communities and provide counseling to indigenous peoples in customary land ownership, so that subsequent customary land sales do not result in losses for indigenous peoples and buyers.